Problems in Adoption of Scientific Agricultural Practices in Agroforestry Home Gardens with Special Reference to Weligama, Sri Lanka - Abeysinghe, M.G.D.; Samaraweera, G.C.; De Zoysa, M. (University of Jaffna, 2023)
Agroforestry home gardens are efficient and sustainable land use stratergies. There are few evidences for detailed analysis of agroforestry homehardens in the literature. Therefore, the present study attempts to assess problems encountered in adopting the scientific practices in agroforestry home gardens with special reference to Weligama Divisional Secretariat (DS), Sri Lanka. Three (03) Grama Niladari (GN) divisions were selected from the DS based on the availability of highest number of agroforestry home gardens. The primary data were collected from randomly selected 30 households from each GN division (n = 90) by personal interviews through the use of a structured questionnaire.Their concern on problems in scientific agriculture practices was measured by 5 point Likert scale ranging from 1 to 5 where 1= Extremely easy,2= Easy, 3=Neutral, 4=Difficult and 5= Extremely difficult. Descriptive and Wilcoxon signed rank test analysis were used to analysis data.The results revealed that majority of households have difficulties in access to scientific knowledge (38.9%), ability to understand scientific knowledge and skills (33.3%), access to reach the government agricultural officers (42.2%) and sufficient facilities to improve scientific knowledge (45.6%).Households mentioned that they are easily (34.4%) acquire scientific knowledge and somewhat difficult (52.2%) to involve government home gardening projects like other requi rements. Further, access to scientific knowledge, ability to have knowledge and skills to understand scientific things, access to reach government agricultural officers, sufficient facilities to improve scientific knowledge, interest to acquire scientific knowledge and other requirement are significantly influenced the problems access score. This study emphasizes the need for well-planned extension programs to promote adoption of scientific agricultural practices in agroforestry homegadens.
Keywords: Agroforestry; Home gardens; Problems